Pemberian aroma terapi pappermint pada ibu hamil TM I dengan masalah mual dan muntah - Setiyawan, Agung Budi; Wardiyah, Aryanti; Wandini, Riska (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2024)
Background: The results of a pre-survey conducted at the Dono Arum Health Center in Central Lampung Regency on 15 pregnant women in the first trimester by conducting free interviews, it was found that 11 mothers (73.3%) had problems with nausea and vomiting with symptoms of nausea in the morning, and after eating or drinking containing fat or oil, and accompanied by vomiting 6-7 times per day accompanied by impaired activity. Meanwhile, 4 mothers (26.7%) experienced mild nausea and vomiting, with a frequency of vomiting 3-4 times per day and were still able to do their activities at home. Purpose: Provide nursing care in nursing care to Mrs. I with the problem of nausea and vomiting through the complementary method of giving peppermint aromatherapy in Dono Arum Village in 2023 Method: This type of research uses descriptive qualitative research, this research uses descriptive research methods in the form of case studies with the Nursing Care approach, which includes assessment, nursing diagnosis, planning, implementation, and evaluation. Results: In this nursing care there are two patients, namely Mrs.D and Mrs.S with the problem of nausea and vomiting in TM I pregnant women caused by smelling unpleasant aromas and unpleasant food, with this the authors to overcome these problems with therapy complementary with peppermint aromatherapy, which has a positive impact on both patients. Keywords: Complementary peppermint aromatherapy; Nausea and Vomiting; Nursing Care. Pendahuluan: Hasil prasurvey yang dilakukan di Puskesmas Dono Arum Kabupaten Lampung Tengah terhadap 15 ibu hamil Trimester I dengan melakukan wawancara bebas, diketahui 11 ibu (73,3%) mengalami masalah mual muntah dengan tanda gejala mual pada pagi hari, dan setelah makan atau minum yang mengandung lemak atau minyak, dan disertai muntah sebanyak 6-7 kali perhari disertai mengalami gangguan aktivitas. Sedangkan 4 ibu (26,7%) mengalami mual dan muntah ringan, dengan frekuensi muntah sebanyak 3-4 kali perhari dan masih bisa beraktivitas dirumah. Tujuan: Memberikan asuhan keperawatan pada asuhan keperawatan pada Ny. I dengan masalah mual dan muntah melalui metode komplementer pemberian aroma terapi pappermint di Desa Dono ArumTahun 2023 Metode: Jenis penelitian ini menggunakan penelitian deskriptif kualitatif, penelitian ini menggunakan metode penelitian deskriptif dalam bentuk studi kasus dengan pendekatan Asuhan Keperawatan, yang meliputi pengkajian, diagnosa keperawatan, perencanaan, pelaksanaan, dan evaluasi. Hasil: Dalam asuham keperawatan ini terdapat dua pasien yaitu Ny. D dan Ny. S dengan masalah mual muntah pada ibu hamil TM I disebebabkan karena mencium aroma aroma yang tidak sedap, dan makanan yang tidak sedap, dengan ini penulis untuk mengatasi masalah tersebut dengan terapi komplemter dengan aromaterapi peppermint, yamg dimna memberikan dampak positif pada kedua pasien tersebut.